A Production systems study on Jacinto Iron and Steel Sheets Corporation - Bango, Emilio H. (College of Engineering, 1996)
Jacinto Iron and Steel Sheets Corporation, with its plant at Quirino Highway, Novaliches and its four provincial warehouses, has been a major supplier of galvanized iron sheets since its founding in 1967. A total production systems study was conducted from February to March 1996 at the said company, the results and recommendations of which are presented herewith. Documentation focused on the following areas: Production Process, Materials Management, Production Planning and Scheduling, and Machine Maintenance. Monthly demand data for years 1991 to 1995 were analyzed using forecasting techniques, and a demand forecast was created for 1996. The plant's actual capacity was computed and compared with the forecast demand volume. From these, it was determined that the plant was capable of meeting the demand on a yearly basis. At a level production rate, there would be a backlog during the months with heaviest demand. Using production planning methods, different aggregate planning alternatives were generated and evaluated. The optimal solution was minimum incremental increase in line speed during these months. Production scheduling rules were formulated to optimize machine utilization. Analysis of the production process and machine maintenance revealed the importance of the accumulator in reducing downtime and non-prime levels. Three different alternatives regarding machine replacement were generated and evaluated; of these the replacement option was recommended. Scrap-level minimization options were drawn up and evaluated. It was recommended that scrap-buying be established on a more frequent basis.